Capital Accumulation, Labor Saving, and Labor Absorption Once More - Williamson, Jeffrey G. (Quarterly Journal of Economics, 1971)
I. Introduction, 40.—II. A neoclassical approach to labor absorption with factor price variability, 42.—III. Asian history and simulation: a look at the models' predictions, 49.—IV. Estimation with Philippine manufacturing data, 54.—V. Conclusion, 64.